Field Evaluation of a Novel Trap Baited with Carbon Dioxide Produced by Yeast for the Collection of FemaleAedes aegyptiMosquitoes in Mexico - Laguna Aguilar, Maricela; Alvarado Moreno, Marcela Selene; Sánchez Rodríguez, Olga Saraí; Ramírez Jiménez, Rocío; Zárate Nahón, Erwy Arvid; Sánchez Casas, Rosa María; Fernández Salas, Ildefonso; Rebollar Téllez, Eduardo Alfonso (Society of Southwestern Entomologists, 2012)
A trap made from low-cost materials and using an attractant of a yeast mixture producing carbon dioxide was designed and evaluated to collect adult Aedes aegypti (L.) mosquitoes. The Trap Mosquito Box prototype was tested against the “standards” BG-Sentinel traps and CDC backpack aspirator in the field. The mean numbers of mosquitoes (± standard deviation) caught by the three different collection methods were: Trap Mosquito Box 2.42 (± 3.08), BG-Sentinel trap 2.86 (± 3.71), and backpack aspirator 0.59 (± 0.90). Statistical tests showed the Trap Mosquito Box and BG-Sentinel trap were equally effective in collecting A. aegypti and both methods were significantly different than the backpack aspirator. Emission of carbon dioxide produced by the yeast mixture was greatest during the first hours after incubation in a laboratory and captured the most mosquitoes in the Trap Mosquito Box. Production of carbon dioxide [Y = -631.24 + 941.26 (log x)] and the rate of mosquitoes captured per time period [Y = 20.29 + 23.50 (log x)] were best explained by logarithmic regressions. Advantages and disadvantages of the Trap Mosquito Box for mosquito surveillance are discussed